Emphysematous pyelonephritis: A rare cause of sepsis in hepatocellular carcinoma. (December 2021) - Wan Hanafi, Hany Haqimi; Mustaffa, Nazri; Lee, Yeong Yeh; Mohd Nawi, Siti Nurbaya
The association between emphysematous pyelonephritis (EPN) and diabetes mellitus is well known. EPN as the cause of sepsis in hepatocellular carcinoma (HCC) is rare and unreported. We report a case of EPN in a non-diabetic HCC patient, in which the clinical features of decompensated chronic liver disease masked the more sinister urological emergency to a certain degree. A computed tomography scan of the abdomen revealed a mixture of gas and fluid in the left retrorenal space, in keeping with left EPN. Nevertheless, the course of clinical deterioration was rather rapid that any surgical intervention was not feasible.